Identification of plasma microRNAs as new potential biomarkers with high diagnostic power in human cutaneous melanoma. Issue 5 (April 2017) - Fogli, Stefano; Polini, Beatrice; Carpi, Sara; Pardini, Barbara; Naccarati, Alessio; Dubbini, Nevio; Lanza, Maria; Breschi, Maria Cristina; Romanini, Antonella; Nieri, Paola
Melanoma is a devastating disease with few therapeutic options in the advanced stage and with the urgent need of reliable biomarkers for early detection. In this context, circulating microRNAs are raising great interest as diagnostic biomarkers. We analyzed the expression profiles of 21 selected microRNAs in plasma samples from melanoma patients and healthy donors to identify potential diagnostic biomarkers. Data analysis was performed using global mean normalization and NormFinder algorithm. Linear regression followed by receiver operating characteristic analyses was carried out to evaluate whether selected plasma miRNAs were able to discriminate between cases and controls. We found five microRNAs that were differently expressed among cases and controls after Bonferroni correction for multiple testing. Specifically, miR-15b-5p, miR-149-3p, and miR-150-5p were up-regulated in plasma of melanoma patients compared with healthy controls, while miR-193a-3p and miR-524-5p were down-regulated. Receiver operating characteristic analyses of these selected microRNAs provided area under the receiver operating characteristic curve values ranging from 0.80 to 0.95. Diagnostic value of microRNAs is improved when considering the combination of miR-149-3p, miR-150-5p, and miR-193a-3p. The triple classifier had a high capacity to discriminate between melanoma patients and healthy controls, making it suitable to be used in early melanoma diagnosis.